Ring laser gyroscopes in the underground Gran Sasso Laboratories. (February 2019) - Beverini, N.; Basti, A.; Bosi, F.; Carelli, G.; Ciampini, D.; Di Virgilio, A.; Ferrante, I.; Fuso, F.; Giacomelli, U.; Maccioni, E.; Simonelli, A.; Stefani, F.; et al.
Abstract: Gyroscopes IN GEneral Relativity (GINGER) is a proposed experiment with the aim of measuring the gravito-electric (known also as De Sitter effect) and gravito-magnetic effects (or Lense – Thirrings effect) in a ground laboratory, foreseen by general relativity, through an array of large dimension ring laser gyroscopes. The site is located inside the Gran Sasso laboratories (LNGS) of INFN, under more than one thousand meter underground, well protected from surface perturbations. GINGERINO is a square ring-laser prototype with 3.6 m side, which has been built to investigate the level of noise of this site. GINGERINO has already completed its task, showing the advantage of the underground location. It cannot reach the sensitivity suitable for the fundamental physics measurements, but it can provide important data for geophysics and seismology. Its high sensitivity in the frequency band of fraction of Hz and its location in a seismically active area make it suitable for seismology studies. It recorded a sequence of central Italy earthquakes in the autumn of 2016 and many other events both from near field and from far field. The analysis of 90 days of continuous operation shows that its duty cycle is higher than 95 %, with a quantum shot noise limit of the order of 10 −10 rad s −1 Hz −1/2 .